Pengaruh Kepemimpinan, Lingkungan Kerja Dan Disiplin Kerja Terhadap Keselamatan Dan Kesehatan Kerja Pada PT Haleyora Power - Nazifah Husainah; Hasanah Hasanah; Mohamad Iswandi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the influence of leadership on occupational safety and health (K3), the influence of the work environment on occupational safety and health (K3), the influence of work discipline on occupational safety and health (K3) and the influence of leadership, environment and work discipline together. the same for occupational safety and health (K3). A quantitative approach is used as this type of research. The population in this study is the project workforce at PT Haleyora Power with 26,215 workers with a sample size of 1,207 workers. The sampling technique used proportional random sampling. The data collection method uses a questionnaire with data analysis through multiple linear analysis. Based on the research results, it was found that the influence of leadership on occupational safety and health was 0.418, the influence of the work environment on occupational safety and health was 0.432, the influence of work discipline on occupational safety and health was 0.418 and the influence of leadership, work environment and work discipline had a simultaneous coefficient on occupational safety and health of 0.910.